CMV Infection Is Directly Related to the Inflammatory Status in Chronic Heart Failure Patients - García-Torre, Alejandra; Bueno-García, Eva; López-Martínez, Rocío; Rioseras, Beatriz; Díaz-Molina, Beatriz; Lambert, José Luis; Quirós, Covadonga; Alonso-Álvarez, Sara; Alonso-Arias, Rebeca; Moro-García, Marco A. (Frontiers in Immunology, 2021)
High levels of inflammation play an important role in chronic heart failure (CHF). Patients with CHF have elevated levels of pro-inflammatory cytokines circulating systemically, mainly TNF and IL-6. However, there are almost no studies that relate these levels to the functional status of patients in CHF, much less to their CMV serostatus. In this study, patients with CHF (n=40; age=54.9 ± 6.3; New York Heart Association functional classification (NYHA, I-III) and healthy controls (n=40; age=53.5 ± 7.1) were analyzed. The serum concentrations of nine pro- and anti-inflammatory cytokines were measured by Luminex® xMap Technology and the basal level of mRNA expression of some immune molecules was quantified by TaqMan™ Array in CD4+ T-lymphocytes. The concentration of these cytokines in culture supernatants in response to anti-CD3 and LPS was also measured. The percentage of CD28null T-cells was determined, as well as the antibody titer against CMV. We found a higher concentration of all cytokines studied in CHF serum compared to healthy controls, as well as a direct correlation between functional status in CHF patients and levels of inflammatory cytokines. Moreover, the highest cytokine concentrations were found in patients with higher concentrations of lymphocytes lacking CD28 molecule. The cytokine production was much higher in CMV+ patients, and the production of these cytokines was found mainly in the T-lymphocytes of CMV+ patients in response to anti-CD3. Anti-CMV antibody levels were positively correlated with cytokine levels. The baseline expression of specific mRNA of the main molecules involved in the Th1 response, as well as molecules related to the CD4+CD28 null subset was higher in CMV+ patients. The cytokine concentrations are higher in CHF CMV+ patients and these concentrations are related to the production of antibodies against CMV. These high levels of cytokines are also associated with the more differentiated CD28null lymphocyte populations. All this, together with the dynamics of the pathology itself, makes CMV+ patients present a worse functional status and possibly a worse evolution of the pathology.